Abnormal pulmonary artery systolic pressure response after exercise in systemic sclerosis patients: A PRISMA-compliant meta-analysis. Issue 6 (February 2019) - Yang, Song; Wu, Jing; Lei, Si; Song, Rong; Cai, Ye-yu; Wu, Shang-jie
Abstract: Background: Pulmonary artery systolic pressure (PASP) is an important parameter for detecting pulmonary arterial hypertension (PAH). The difference between rest PASP and post-exercise PASP (ΔPASP) may play a role in predicting and screening resting PAH. The aim of this study is to analyze ΔPASP in systemic sclerosis (SSc) patients with PAH or non-PAH and suggest a cutoff value of ΔPASP for detection of PAH. Methods: PubMed, Embase, and Web of Science were searched for relevant publications up to July 7, 2018. Characteristics of control, no PAH, exercise-induced PAH (EIPH) and PAH subgroups in SSc patients were extracted. R 3.5.0 with the "meta" package was used to conduct this meta-analysis. Results: Twelve articles involving 1279 patients were included in this study. The subgroups meta-analysis showed pooled mean ΔPASP in different subgroups: control group (8.6 mmHg, 95% CI: 6.9–10.5), no PAH group (12.2 mmHg, 95% CI: 11.2–13.2), EIPH group (26.0 mmHg, 95% CI: 24.2–27.7) and PAH group (36.2 mmHg, 95% CI: 29.7–42.7). Conclusion: Combining the results of our study with the previous studies, an abnormal increase in PASP after exercise could indicate the development of PAH in SSc patients. In addition, if ΔPASP>29 mmHg, a high suspicion of PAH should be raised.